2022
DOI: 10.3390/ma15051625
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Defects of Two-Dimensional Layered Carbon/TiO2 Superlattice Composite for a Fast Lithium-Ion Storage

Abstract: Defect engineering is one of the effective ways to improve the electrochemical property of electrode materials for lithium-ion batteries (LIB). Herein, an organic functional molecule of p-phenylenediamine is embedded into two-dimensional (2D) layered TiO2 as the electrode for LIB. Then, the 2D carbon/TiO2 composites with the tuning defects are prepared by precise control of the polymerization and carbothermal atmospheres. Low valence titanium in metal oxide and nitrogen-doped carbon nanosheets can be obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This can promote the vertical diffusion of K ions and provide sufficient electrochemical active sites, leading to a high specific capacity. [ 39 ] However, the increased surface disorder of the MOF‐NOC@L‐TiO 2 inevitably leads to a decline in conductivity. Hence, the highest capacity can be achieved with just a moderate number of defects.…”
Section: Resultsmentioning
confidence: 99%
“…This can promote the vertical diffusion of K ions and provide sufficient electrochemical active sites, leading to a high specific capacity. [ 39 ] However, the increased surface disorder of the MOF‐NOC@L‐TiO 2 inevitably leads to a decline in conductivity. Hence, the highest capacity can be achieved with just a moderate number of defects.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electronic conductivity of the pellet did not rise in tandem with the further increased pPDA ratio, indicating that the conductivity of NTO/Gr is higher than that of carbonized pPDA at 500 °C. [52] Meanwhile, we assembled coin cells for electrochemical performance comparison. Figure S7c depicts the rate curves of NTO/Gr + PA%, and we can determine that NTO/Gr-1PA has the best rate performance and the highest specific capacity.…”
Section: Resultsmentioning
confidence: 99%
“…It can be shown that LLTO@C-500/600 contain a high content of graphene nanosheets after the carbonization reaction. Besides, the electronic conductivity test of the layered LLTO@C composites was carried out according to our previous work by using a two-electrode blocked cell within a voltage range from −0.2 to 0.2 V, 34 which can explain the improved electrical conductivity of the 2D nanosheets which is highly beneficial for the rapid electronic transportation and power delivery. According to the conductivity formula: σ (S m −1 ) = L / RS , where S (m 2 ) is the cross-sectional area, R (Ω) is the resistance value and L (m) is the length.…”
Section: Resultsmentioning
confidence: 99%